(3Yjf GdMjGI aj Yde GSJfHGW GdejGgs - (3GdOefghQj , CMeO Hf YHO GdefYe Hf jhSa Hf UjGe GdOefghQj, SQGL GdOjf,J (B1192 (3g` s ((3YHOGdaJGM LGO Gdehdi CHj GdaJM GdOdLi GdTGaYi s)
(3ChdgG (B:s
(3hHYO, gPG eG GdJeS efi hGMO GdeMbjbjf jhSa Hf eMeO GdRZhGfi GdJhfSi GdMfai s
(3BNQgG (B:s
(3ef GdKGfi YTQ (B(12 (3LeGOi GdChdi SfI (B1146) (3ef GdgLQI GdfHhjI Ydi UGMHgG CaVd GdUdGI hGdSdGe s
(3HgG LOGhd hCTcGd hUhQI degGH GdQjGM hGdcQI GdCQVjI hGdCbGdje GdSHYI hZjQgGs
(3YdjgG JUMjMGJ HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B164 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B303s
Keywords: (3GdcjejGA h GdWHjYjGJs